Investigating the Relationship Between Institutional Quality and Ecological Footprint in Türkiye - Kirikci, Muhammet Bahri (Sosyoekonomi Soc, 2025)
In today's world, where the climate crisis is deepening, one of the critical problems is preventing environmental pollution. In this context, the study examines the role of institutions on the environment to develop a different perspective on the problem of preventing environmental pollution. In line with this goal, an empirical examination was conducted in T & uuml;rkiye between 1984-2022 using ARDL, DOLS, FMOLS and CCR techniques. In addition, the causality relationship between variables is examined with the Toda Yamamoto Causality Test. According to the findings of the study, institutional quality reduces environmental pollution. On the other hand, in this study, where the pollution haven hypothesis is tested, it is accepted that this hypothesis is valid in the long term. It is determined that there is a bidirectional causality relationship between corporate quality and ecological footprint.
Türkiye’de Kurumsal Kalite ve Ekolojik Ayak İzi İlişkisinin İncelenmesi
Keywords: Institutional Quality; Ecological Footprint; T & uuml;rkiye; ARDL; DOLS; FMOLS; CCR; Toda Yamamoto Causality Test